Analisis Yield Bahan Bakar Cair pada Pirolisis Ban Luar Sepeda Motor Dengan Katalis ?-Alumina dengan Pendekatan Anova - Erlinda Ningsih (Institut Teknologi Adhi Tama Surabaya, 2021)
ABSTRACT In the rainy season the accumulation of tire waste has the potential to become a breeding ground for mosquitoes and animals that have the potential to spread disease, while in the dry season the accumulation of waste is very vulnerable and has the potential to cause fires that produce toxic gases that are harmful to the environment. Pyrolysis can be an alternative solution to reduce the amount of tire waste by converting it into alternative fuels. Pyrolysis was carried out using waste tires and motorcycle tires with -alumina as catalyst. The purpose of this study was to analyze the effect of reactor temperature and ratioalumina catalyst ratio on liquid fuel yield using the ANOVA approach. The pyrolysis process lasted for 2 hours with variations in reactor temperature, namely 400oC, 450oC, and 500oC. Variations in the ratio of catalyst and tire are 1:100, 3:100, 5:100, and without catalyst. The results of the analysis using the Anova approach concluded that the reactor temperature and the catalyst ratio had an effect on the yield of the outer tire liquid fuel. At a ratio of 5:100 and a temperature of 500oC produces the largest yield of 35.34%Keywords: pyrolysis, ?-alumina, tires, fuel, Anovaa, tires, fuel, Anova